Pneumococcal-meningitis associated acute disseminated encephalomyelitis (ADEM) – case report of effective early immunotherapy - Huhn, Konstantin (Springer International Publishing, 2014)
INTRODUCTION: Unvaccinated patients with history of splenectomy are prone to fulminant courses of Streptococcus pneumoniae-associated bacterial meningitis. Besides direct brain damage those patients may additionally suffer from parainfectious syndromes, notably vasculitis and acute disseminated encephalomyelitis (ADEM). Differentiation and treatment of these immunological reactions is challenging. METHODS: Case report. RESULTS: A 61 year-old woman with history of splenectomy without vaccination for S. pneumoniae presented with progressive headache and meningism. CSF-analysis revealed pleocytosis with microbiological evidence for pneumococcal meningitis. After unsuspicious initial cranial CT imaging and initiation of appropriate antibiotic therapy, MRI two days later showed widespread FLAIR- and T2-hyperintense white matter lesions that further progressed upon follow-up MRI and that fulfilled imaging criteria of ADEM. Meanwhile the patient deteriorated and required mechanical ventilation. Cranial angiography showed no signs of vasculitis or vasospasms. Screening for autoimmune diseases remained negative, however oligoclonal bands turned positive. Brain biopsy mainly revealed perivascular CD4+ T-cells and demyelinated areas. Despite ongoing acute meningitis, a 10-day corticosteroid-pulse was initiated followed by steroid-tapering. Within 4 weeks, clinical and MRI findings ameliorated. In an one-year follow-up visit, the patient significantly recovered, MRI lesions were markedly reduced and no further relapses occurred. CONCLUSION: Acute pneumococcal meningitis in unvaccinated splenectomized patients may be complicated by a monophasic course of parainfectious ADEM that can be controlled with high-dose corticosteroids. Parainfectious vasculitis or cerebritis are important differential diagnoses and exact differentiation of these entities is important to initiate early appropriate immunotherapy.